Reexamination of hemoglobin adjustments to define anemia: altitude and smoking. Issue 1 (23rd June 2019) - Sharma, Andrea J.; Addo, O. Yaw; Mei, Zuguo; Suchdev, Parminder S.
Abstract: The correct interpretation of hemoglobin (Hb) to identify anemia requires adjusting for altitude and smoking. Current adjustments were derived using data collected before 1985, from low‐income preschool‐aged children (PSC) in the United States and indigenous men in Peru for altitude, and from White women of reproductive age (WRA) in the United States for smoking. Given the oldness and limited representativeness of these data, we reexamined associations between Hb and altitude and/or smoking using 13 population‐based surveys and 1 cohort study each conducted after 2000. All WHO regions except South‐East Asia were represented. The dataset included 68, 193 observations among PSC (6−59 months) and nonpregnant WRA (15−49 years) with data on Hb and altitude (−28 to 4000 m), and 19, 826 observations among WRA with data on Hb and smoking (status or daily cigarette quantity). Generalized linear models were used to assess the robustness of associations under varying conditions, including controlling for inflammation‐corrected iron and vitamin A deficiency. Our study confirms that Hb should be adjusted for altitude and/or smoking; these adjustments are additive. However, recommendations for Hb adjustment likely need updating. Notably, current recommendations may underadjust Hb for light smokers and for those residing at lower altitudes and overadjust Hb for those residing at higher altitudes. Abstract : In 2001, the WHO established hemoglobin (Hb) concentration cutoffs to define anemia that included adjustments to account for altitude and smoking. Given the oldness and limited representativeness (i.e., geographic, age, and race) of the data used to establish the adjustments, our objective was to examine the association between Hb and altitude and/or smoking among diverse population groups using more recent (since 2000), multinational data in an effort to evaluate current WHO recommendations for adjusting Hb for altitude and smoking.